The DEVELOPMENT OF SAVONIUS VERTICAL-AXIS WIND TURBINE PROTOTYPE BASED ON MICROCONTROLLER - Zulhajji, Zulhajji; Suhardi, Iwan; Sadri, Abdul Rijal (Jurnal Media Elektrik, 2025)
This research focuses on the development of a valid prototype of the Savonius vertical axis wind turbine model through a research and development (R&D) approach, using a modified Borg and Gall development model. The study introduces a functional prototype suitable for student learning in renewable energy courses, offering a simpler and more portable alternative to wind energy generation. Student responses showed a positive perception, with 53% stating that the Savonius wind turbine was suitable for the presentation. The results of the questionnaire showed an overall average score of 86%, which was categorized as "Very Appropriate". The turbine operates effectively at a minimum wind speed of 3.5 m/s, producing an average voltage of 10.28 V, a current of 10.46 mA, and an output power of 1 watt. Although relatively small, this power level is sufficient for small-scale applications, highlighting the prototype's ability to support devices with low power or simple lighting, as well as serving as a renewable energy education tool. Wind turbine performance analysis showed optimal results at an average wind speed of 3.88 – 4.84 m/s, a power coefficient (Cp) of 0.87, and a tip-speed ratio (TSR) of 0.82. This shows a direct correlation between the TSR and the power coefficient, which indicates efficient turbine performance.